Adverse events in adult intensive care units: an integrative review (Research, Society and Development, 2021)
Care in an Intensive Care Unit (ICU) is intended for critically ill patients, who, due to their complexity, are more exposed to the occurrence of adverse events (AE), usually resulting from health care such as phlebitis, medication errors and Pneumonia associated with mechanical ventilation. These AEs can cause temporary or permanent damage and their occurrence is linked to multiple factors related to the patient and work processes. It aimed to identify scientific evidence on the most frequent adverse events in ICUs. Integrative review performed in Mediline, Scopus, Scielo and Lilacs databases between April and May 2021 with a time frame from 2016 to 2021. 10 articles published in English and Portuguese were included. The results showed that the most frequent adverse events are linked to health care, highlighting the clinical processes/procedures and that there are factors that influence the occurrence of events such as: age, comorbidities, severity, greater nursing workload, disproportionate staffing. Although adverse events are considered a public health problem that is very present in intensive care units, there are still few studies on the subject.